(untitled) (New York, NY., 1996)
Designed for students in grades five through eight, this illustrated dictionary of the English language contains more than 50,000 definitions as well as pronunciation guides, word origins, synonyms, maps, and other features
Keywords: English language,English language; Dictionaries, Juvenile.,Dictionaries